A comparative study of the pragmatic competence of native and non-native speakers of English / Amir Boudaghi - Boudaghi, Amir (2015)
Pragmatics is a field of knowledge that can be recognized in a socio-cultural context of study in intercultural communication. The present research aimed at conducting a comparative study on the native and non-native speakers’ pragmatic competence of the English language in the University of Malaya. The study mainly focused on studying the pragmatic knowledge of Malaysian Chinese on the two speech acts of apology and request in the academic level, and comparing their performance with that of the English native speakers working in University of Malaya. To do so, following a thorough review of the related literature a pilot study was done based on a previously developed Multiple-Choice Discourse Completion Test (MDCT), and then 80 Malaysian Chinese studying in University of Malaya as the Non-native speakers and 20 North American Native speakers studying or working in the academic situations at the same university received the test which mainly focused on two speech acts of request and apology. The comparison of the testees’ performances on the test given firstly revealed that the participants’ performance on the test was the same for the pragmatic test of apology and request. Thus it was concluded that both native and non-native speakers were able to answer the items referring to both speech acts of the study with no preference. Secondly, there was a significant difference between the performance of native and non-native learners on the MDCT of apology and request; consequently it was revealed that native speakers showed a significantly higher performance on the MDCT of apology and request. It was concluded that NNSs need to gain mastery over various speech act strategies to show they are pragmatically competent and ready to accomplish effective negotiations or communications in the real langue situations at the academic level. The study findings also revealed that NNSs taking part in the study were not competent enough to perform as effectively as the NSs. This means that the NNSs need training in terms of their pragmatic competence and this point might have been neglected in the previous training of the learners of the present study. The findings of the study could be employed by ESL/ EFL teachers, policy makers, and material developers to pay more attention to teaching pragmatic competence to the learners and make them more aware of the real target language situations.